Factors associated with the adoption of drinking and driving during a zero tolerance period: results from a 6-years study in the GAZEL cohort. (1st March 2011) - Constant, A; Encrenaz, G; Lafont, S; Chiron, M; Lagarde, E; Messiah, A
Abstract : Background: While dropping Driving While Alcohol-Intoxicated (DWI) might be interpreted as a success of prevention initiatives, its adoption during a zero-tolerance period might jeopardise efforts to improve road safety. The study objectives were as follows: (1) to estimate frequencies of behaviour change regarding DWI between 2001 and 2007; and (2) to determine which factor changes that had occurred by 2001 were associated with consistent DWI adoption in the subsequent 2004–2007 period. Method: We conducted a prospective study in a large cohort of French employees and retirees (the GAZEL cohort). A Driving Behaviour and Road Safety (DBRS) questionnaire was administered three times, in 2001, 2004 and 2007. Results: The population comprised 9309 participants. In 2001, 2171 participants reported DWI while 7138 reported sober driving. More than one drink-driver out of five quitted DWI between 2001 and 2007 (n=462), while 8.2% of safe drivers adopted this behaviour (n=511). When adjusted for potential confounders, the risk of adopting DWI was associated with: increased alcohol consumption, increased number of close friend, decreased number of relatives and decreased attitudes in favour of enforcement/regulations. Discussion: The recent crackdown on road violations taken by French government in 2002 has deterred a substantial part of offenders to continue DWI, but this success was compromised by the occurrence of new drink drivers. Preventive strategies should aim at modifying factors that facilitate DWI adoption, in particular increased alcohol consumption and low acceptance of law enforcement.